THE IMPACT OF CHROME PLATED COPPER CATALYTIC CONVERTERS ON ENGINE PERFORMANCE WAS EVALUATED BY CHASSIS DYNAMOMETER EXPERIMENT - Sudirman Rizki Ariyanto; Retno Wulandari; Suprayitno Suprayitno; Muhammad Yandi Pratama; Ata Syifa’ Nugraha (Media Mesin: Majalah Teknik Mesin, 2023)
Emissions produced by motorized vehicles greatly contribute to various environmental and health problems. One technology that is currently being developed to reduce the number of emissions in the environment is the catalytic converter. This technology is proven to be able to reduce exhaust emissions well, but how big the impact on engine performance (torque and power) still needs further research. The main objective of this study was to determine the impact of using chrome plated copper (CuCr) catalytic converters on engine performance. The vehicle used in the test is a Yamaha Vixion Lightning 150 CC. Engine performance (torque and power) was measured using the Inertia Chassis Dynamometer test instrument with the SAE J1349 standard. The findings of this study indicate that the use of experimental exhaust results in a decrease in vehicle torque and power. This is certainly a compromising factor that must be accepted, considering that installing a catalyst is the same as increasing the exhaust gas flow barrier. The decrease in torque and power is still in the acceptable category, considering that the average decrease only occurs at about 5% for torque and 7% for power. All these arguments show that since the main purpose of using catalytic converters is to lower exhaust emissions, it makes engine performance lower than expected.